Efektivitas Trichoderma spp. sebagai Pengendali Hayati terhadap Tiga Patogen Tular Tanah pada Beberapa Jenis Tanaman Kehutanan - S. M. Widyastuti; Sumardi Sumardi; P. Sumantoro (Jurnal Perlindungan Tanaman Indonesia, 2001)
The experiment was aimed to compare Trichoderma spp. with fungicides in the control of soil-borne pathogens and to evaluate the inhibitory effect of the fungicides on the activity of Trichoderma spp. The first objective was achieved by applying antagonistic test of three isolates of Trichoderma spp. and inhibitory growth test of fungicides both against soil-borne pathogens. The second objective was attained by growing Trichoderma spp. on growth medium containing four level of fungicides.